2010
DOI: 10.1016/j.rpor.2010.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cell sarcoma: Response to radiotherapy

Abstract: We present the case of a patient with progressive Langerhans cell sarcoma whose cutaneous lesions and nodal masses were treated with palliative radiotherapy. Response to relatively low doses of radiotherapy was both good and sustained. We recommend a dose of 15-30 Gy depending on treatment intention and volume of the lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Efficacy was also reported for MAID (Mesna, doxorubicin, ifosfamide, dacarbazin) [153], or cladribin (2-CDA) followed by ESHAP (etoposide, carboplatinum, cytarabin, methylprednisolone) [107]. Radiotherapy has at least a palliative effect [125]. In case BRAF mutations are found, the use of BRAF inhibitors may become a potential strategy [201].…”
Section: Langerhans Cell Sarcoma (Lcs) Langerhans Cell Mhmentioning
confidence: 99%
“…Efficacy was also reported for MAID (Mesna, doxorubicin, ifosfamide, dacarbazin) [153], or cladribin (2-CDA) followed by ESHAP (etoposide, carboplatinum, cytarabin, methylprednisolone) [107]. Radiotherapy has at least a palliative effect [125]. In case BRAF mutations are found, the use of BRAF inhibitors may become a potential strategy [201].…”
Section: Langerhans Cell Sarcoma (Lcs) Langerhans Cell Mhmentioning
confidence: 99%
“…Lucas et al reported that radiation therapy also has the potential to shrink tumour lesions [35]. They found that LCS responds well to radiotherapy and believe that irradiation is a good option in selected cases with symptomatic or bulky lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cell infiltration, consisting of lymphocytes and eosinophil gran- Table I. Summary of the reported cases of Langerhans cell sarcoma [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35] ulocytes, was also found, and isolated mitotic figures were identified ( Fig. 3A and 3B).…”
Section: Case Presentationmentioning
confidence: 95%
“…The management of LCS has also differed widely ranging from single modality (generally in cases with localized involvement); to combination therapy including surgery and/or chemo-radiotherapy, albeit no consensus exists on the sequence of the choice of therapy. In one reported case, Lucas et al noted a relapse after 3 months of therapy with CHOP (cyclophosphamide, doxorubicin, vincristine and prednisone) and thereafter successfully treated the cutaneous lesions and nodal masses with palliative radiotherapy [12]. Bone marrow transplant has also been attempted and correlates to good outcomes in carefully selected patients, generally in the relapsed setting [13].…”
Section: Discussionmentioning
confidence: 99%